122k views
5 votes
2ax-b=cx+d solve for x

1 Answer

6 votes

We have to solve the following equation for the variable x:


2ax-b=cx+d

For doing so, we assume that the variables a, b, c and d behave as normal numbers, and we will move the terms with x to the left side, and those who doesn't have it, to the right.


\begin{gathered} 2ax-b-cx=cx+d-cx \\ 2ax-cx-b=d \\ 2ax-cx-b+b=d+b \\ 2ax-cx=d+b \end{gathered}

Now, we will factor the variable x, as we want to have just one expression with x, thus:


(2a-c)x=d+b

And lastly, we will divide both sides by 2a-c, and we obtain:


x=(d+b)/(2a-c)

Which is the asked expression for x.

User Wooer
by
5.4k points